Ecotourism as Tourist Attraction Development: Systematic Literature Review - Sumihar Sebastiana Sitompul (Jurnal Penelitian Pendidikan IPA, 2024)
Ecotourism is a form or concept of special interest tourism because it can be said to be the opposite of mass or conventional tourism. In managing ecotourism, nature and its environment are the main resources that must be managed carefully. The Quebec Declaration explains that ecotourism is a form of tourism that adopts the principles of sustainable tourism which differentiates it from other forms of tourism. In practice, it can be seen in the form of tourism that actively contributes to nature and cultural conservation activities, involves local communities in planning, developing, and managing tourism and makes a positive contribution to their welfare, and is carried out in the form of independent tourism or organized in the form of small groups. Where is the research objective? is to study ecotourism as tourist attraction development: Systematic Literature Review. This review was conducted based on state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. The results of this research explain that there are several principles for developing ecotourism, namely conservation principles, community participation principles, and economic principles; The impact of ecotourism development, namely: The impact of ecotourism on social aspects, The impact of ecotourism on economic aspects and the Ecotourism development strategy, namely: Identifying factors that influence the development of ecotourism, Determining several key factors in ecotourism development which are studied based on discussions with ecotourism experts, institutional experts and study of literature.”